ANALISIS POTENSI PASAR DAN STRATEGI PEMASARAN UNTUK PRODUK ATAU LAYANAN INOVATIF TERHADAP USAHA COFFEESHOP LATERA JAMBI - Fitrah, M. Afif Vilano (Jurnal Manajemen Pendidikan, 2025)
This study seeks to examine the impact of market analysis, product innovation, and marketing communication strategy on the marketing performance of Coffeeshop Latera Jambi, along with the mediating effect of the quality management system in these dynamics. This is a causal research employing a quantitative methodology. Data were gathered via questionnaires administered to 225 patrons of Coffeeshop Latera Jambi and analyzed utilizing Structural Equation Modeling-Partial Least Square (SEM-PLS). The findings indicate that market analysis, product innovation, and marketing communication strategy significantly improve the marketing performance of Coffeeshop Latera Jambi. Moreover, the quality management system mediates the effects of these variables on marketing performance.  This study offers a novel contribution by revealing the mediating role of the quality management system in enhancing the effectiveness of marketing strategies within a local coffeeshop context, particularly Coffeeshop Latera Jambi, which has been underexplored in previous research.